Cooling load minimization and the thermal comfort in typical structure / Mohd Saiful Rizal Muhamad ... [et al.] - Muhamad, Mohd Saiful Rizal; Azmi Murad, Adlan Mossley (1999)
Indoor climate should be adjusted to human need by opening windows or using fans in summer. However system are capable of being varied to meet almost any comfort or industrial demand, anywhere on earth with precise automatic control.